Author Under Sail : The Imagination of Jack London, 1902-1907 - Williams, Jay (James W.) (Book collections on Project MUSE., 2021)
In this second volume of Author Under Sail Jay Williams investigates the life of Jack London as a professional writer at the turn of the 1900s, as his publications spanned The Call of the Wild to The Iron Heel and The Road. While documenting key life events, especially his rising fame, this biography explores London's necessity to illustrate the inner workings of his own vast imagination through his socialist essays and fiction.